A biopsychosocial framework for recovery from COVID-19. Issue 9 (22nd September 2020) - Stuart, Kaz; Faghy, Mark A.; Bidmead, Elaine; Browning, Ruth; Roberts, Catriona; Grimwood, Sam; Winn-Reed, Thea
Abstract : Purpose: This paper proposes a biopsychosocial (BPS) analysis of COVID-19 experiences which enhances understanding of complex and interrelated factors and leads to the proposition of a BPS recovery framework. Design/methodology/approach: Online narrative research was used to explore people's experiences of COVID-19 and was conducted over a four-month period. The call was distributed via a short open-ended qualitative online survey advertised on social media platforms and 305 responses came from across England. Findings: The findings illustrate people with a narrow range of BPS characteristics experienced over a wide range of BPS impacts which are nuanced, complex and dynamic. Left unaddressed these may create future adverse BPS characteristics. An integrated BPS framework for recovery is proposed to avoid such further negative outcomes from the pandemic. Research limitations/implications: The sample contained a bias in age, gender and living arrangements. Practical implications: The paper offers a clear framework to enable integrated holistic recovery/regrowth planning. Social implications: Using the framework would reduce social and health inequities which have been recently deepened by COVID-19 in the long-term. Originality/value: The paper is original in its use of a BPS analytical framework.